PERCEPATAN PENETAPAN DAN PENEGASAN BATAS DESA DI KABUPATEN LAMANDAU TAHUN 2024 BERBASIS KEARIFAN LOKAL (BAHAUM BAKUBA) - Puji Rahmat Pratama; Riban Satia; Irwani, Irwani (Yayasan Nusantara Hasana Berdikari, 2025)
This research discusses the acceleration of the determination and confirmation of village boundaries in Lamandau Regency in 2024, using a local wisdom-based approach. In the context of regional autonomy, village boundaries are an important element that defines government administrative areas and functions to create legal certainty and administrative order. This research identifies the technical and social obstacles faced in the process of confirming village boundaries, as well as their impact on village development. The method used is descriptive qualitative, with data collection through observation, interviews and documentation. The results of the analysis show the need to increase the capacity of village governments and communities, use technology in boundary setting, and develop supporting policies. Collaboration between the government, traditional institutions and local communities is essential to ensure the legitimacy and sustainability of the village boundary delimitation process. Thus, this research provides strategic recommendations to accelerate the process of establishing effective and sustainable village boundaries.